Effect of integrated yoga and naturopathy intervention on psychological states and quality of life in a patient with irritable bowel syndrome: a single case report - Alkousar Taz Mujeebullah; Bharanidharan Ravi; Srisathya Seshan Venkatesan; Kalavathi Subramaniam Dhamodhini; Renjish Mohanan (International Journal of Basic & Clinical Pharmacology, 2026)
Irritable bowel syndrome (IBS) is a chronic disorder of gut-brain interaction characterized by abdominal pain, altered bowel habits, and significant psychological distress, which adversely affect quality of life. The present case report describes the effect of an integrated Yoga and Naturopathy (Y and N) intervention on psychological well-being and quality of life in a patient with IBS associated with autoimmune comorbidities. A 57-year-old male with a 25-year history of IBS and a 40-year history of vitiligo presented with epigastric pain, altered bowel habits, anxiety, depression, and reduced quality of life. He had a strong family history suggestive of autoimmune predisposition and was receiving pharmacological treatment for multiple conditions. The patient underwent a 10-day residential Y and N program comprising yoga practices, pranayama, deep relaxation techniques, hydrotherapy, mud therapy, acupuncture, massage therapy, reflexology, cleansing procedures, and a plant-based naturopathic diet. Psychological well-being and quality of life were assessed using the generalized anxiety disorder-7 (GAD-7), patient health questionnaire-9 (PHQ-9), and IBS quality of life (IBS-QOL) scales before and after the intervention. Following the intervention, anxiety scores decreased from 18 to 10, depression scores reduced from 14 to 4, and IBS-QOL scores improved from 57.3 to 69.9. The patient also demonstrated reductions in body weight and body mass index and reported discontinuing long-term symptomatic medications, with a subjective improvement in overall well-being. This case suggests that integrated Y and N interventions may improve psychological health and quality of life in patients with IBS and associated autoimmune conditions. Further large-scale studies are warranted to validate these findings.